If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + 2 + -7 = 0 Reorder the terms: 2 + -7 + 5n = 0 Combine like terms: 2 + -7 = -5 -5 + 5n = 0 Solving -5 + 5n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 5n = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 5n = 0 + 5 5n = 0 + 5 Combine like terms: 0 + 5 = 5 5n = 5 Divide each side by '5'. n = 1 Simplifying n = 1
| 8(4x-2.5)=16 | | 4+-0.5y=x | | 3(1-x)=-(7x+5) | | 4(z+2)-7z=6(-0.5z+1)+2 | | 5(5c-1)-1=20c+4 | | 4-3[q]=10 | | 65(2x-5)=180 | | Cos(45+x)=.42cos(45-x) | | 8(4-2.5)=16 | | 11(-3x+2)-2(1-5x)=-7x-6x | | 9(4-2n)-3=4-6(3n-5) | | 3ln(x+2)-5ln(5x)=x | | .6x+5=3 | | -5r-5(5+5r)=-5(2+7r) | | -4.0x+2.7-16x=-4.6x+2.7 | | 2x-160250-160250=320420-160250 | | x^2y-X^2+4y-9=0 | | 8+(-8)=-8-8 | | 17x-4y=29 | | -5(-3.25)=4m+8 | | (2t-5)(6t+1)=(4t-3)(3t+6) | | 2c+3=3-4 | | 4(6.25)+3k=34.60 | | 2x-23+2x-17=8 | | Z^2-(i+1)*z+i=0 | | 5x*9-7=3 | | 12-5(3(-1)+2)=17 | | 9(2n)-3=4-6(3n-5) | | 3x^2-36x-27=0 | | 4m+4+7m=13+8m | | 11(-3x-2)-2(1-5x)=-7x-6x | | 5345+n=288195 |